A case series of Covid-19-associated fungal infections: The gruesome twosome (Indian Journal of Case Reports, 2022)
Severe Acute Respiratory Syndrome Coronavirus-2(SARS-CoV-2) is the novel coronavirus responsible for causing Coronavirus disease (COVID-19). The pandemic has seen many ebbs and flows since its detection, particularly regarding various manifestations coupled with it. Secondary fungal infections, especially COVID-19-associated mucormycosis, have seen a summit, especially during the second wave of the pandemic. However, we reported a series of three cases of mucormycosis in association with another fungal mould from the sample received from patients infected with this virus that presented to our hospital during this pandemic. Our report is about the novelty of dual fungal infection caused by a Zygomycete group along with Aspergillus isolated from pulmonary as well as extra-pulmonary sites, all of which were confirmed on culture. Timely and multidisciplinary management of these patients helped patient survival.